On Fuzzy Congruences and Fuzzy Strong h-Ideals of Hemirings - Kuanyun Zhu; Jianming Zhan; Yunqiang Yin (The Scientific World Journal)
The aim of this paper is to introduce the concepts of fuzzy strong h-ideals and fuzzy congruences of hemirings. The quotient hemirings via fuzzy strong h-ideals are investigated. The relationships between fuzzy congruences and fuzzy strong h-ideals of hemirings are discussed. Pay attention to an open question on fuzzy congruences. Finally, the normal fuzzy strong h-ideals of hemirings are explored.